PENINGKATAN KETERAMPILAN MENULIS RINGKASAN TEKS CERITA ANAK MELALUI STRATEGI CATATAN JENDELA PADA SISWA KELAS IV A SDN BANJARBENDO SIDOARJO - Hakiky, Ade Bella (Journal Of Islamic Elementary School (JIES), 2019)
The purpose of this study was to determine the application of the window record strategy to improve student learning outcomes in class IV A Banjarbendo Sidoarjo Elementary School after the implementation of the window note strategy model in the competence of writing text summary stories. This class action research method uses the Kurt Lewin model which is carried out in 2 cycles. Data collection techniques in the form of interviews, observation, product assessment, and documentation. The results of the study show that: (1) The implementation of the window record strategy has been applied according to the plan. This is evidenced by the increase in the results of research on teacher activity in the first cycle of obtaining a score of 75 (good) to 88.33 (very good) in the second cycle. It was also proven by the increase in student activity results from the acquisition of a score of 78.94 (good) in the first cycle to 91.22 (very good) in the second cycle. (2) Increasing the skill of writing story summary text through a window note strategy has increased. This can be seen from the average value of students in the pre cycle of 63.5 (enough) with the percentage of learning completeness 43.33% (very lacking), changing to 70.17 (good) with the percentage of learning completeness 63.33% (enough) in the first cycle, and to be 80.5 (good) with the percentage of learning completeness 93.33% (very good) in the second cycle.